THE IMPACT OF BRAND IMAGE, FOOD LABEL, PRODUCT QUALITY AND CONTENT MARKETING ON CONSUMER PURCHASING DECISION OF IMPORTED SNACK: Study on Tao Kae Noi Consumers in Semarang - Annisa, Fathia Nur; Kusumawardhani, Amie (Diponegoro Journal of Management, 2024)
ABSTRACT The popularity of snacking among Indonesian consumers is rising gradually. This is supported by the food and beverage industry’s impressive performance growth over the several years. As a result of the rising competition, Tao Kae Noi will be forced to remain competitive, develop their brand image and product quality, as well as improving their consumer purchasing decisions by utilizing food label and content marketing trends. This study was conducted to observe the influence of brand image, food label, product quality, and content marketing on consumer purchasing decisions of Tao Kae Noi consumers. The population in this study are the consumers of Tao Kae Noi products located in Semarang, Indonesia. The samples taken were 129 respondents. The sample collecting method used is purposive sampling. The data collecting method used was distributing questionnaires through Google Form. The analysis method used in this study was Multiple Linear Regression using SPSS 25 as the analysis tool. The findings from this study indicate that brand image, food label, product quality, and content marketing partially and simultaneously have positive and significant influence on consumer purchasing decision. In addition, content marketing has the biggest influence on purchasing decision of Tao Kae Noi products.